Morphological and molecular characterization of Fusarium sp. causing Bakanae disease of rice (Oryza sativa) in western Uttar Pradesh, India - BAG, DIPANJALI; KHILARI, KAMAL; KUMAR YADAV, AMIT; SINGH, ARJUN; SINGH, PRASHANT (The Indian Journal of Agricultural Sciences, 2022)
Rice (Oryza sativa L.) is considered as one of the main staple food grains. The Asian countries lead in production and consumption of rice i.e. more than 90% rice is produced and consumed in Asia. India is considered as one of the leading exporters of rice. Rice is affected by number of diseases and pests and among the several diseases which infects the rice crop, a fungal disease commonly known as Bakanae disease or Foot rot of rice is caused by Fusarium moniliforme (Gibberella fujikuroi) fungus. It is one of the important diseases of rice and leads to severe losses in rice yield particularly in basmati rice. According to some previous reports, some other Fusarium species were also found to be causing the disease. Therefore, the following study was conducted in the year 2018–19 at Sardar Vallabhbhai Patel University of Agriculture & Technology, Meerut, Uttar Pradesh, India, to find out and identify the Fusarium sp.mainly associated with the Bakanae disease in western Uttar Pradesh. Twelve isolates of Fusarium moniliforme were collected and isolated from different locations of western Uttar Pradesh and their characterization of morphological and molecular characters was carried out. Morphological characters, like fungal growth type, pigmentation, radial growth, colony characters were studied and compared with the standard culture of Fusarium moniliforme obtained from ITCC, New Delhi. The molecular characterization was done with specific primers. The results indicated that Bakanae disease of rice in western Uttar Pradesh is primarily caused by Fusarium moniliforme. The study also confirms that identification based on morphological and culture characteristics must be coupled with molecular characteristics for proper identification of specific fungal sp. causing Bakanae disease